2017
DOI: 10.12691/aees-5-2-5
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Sustainability Rate of Cropping Systems Commonly Used in Jahrom Region, Fars Province, Iran

Abstract: Maintenance and sustainability of agricultural products sources are considered as the significant principles of sustainable agriculture while healthy products and continuity in production are dependent on the development of sustainable agriculture. The main purpose of this study is to evaluate the sustainability rate of cropping systems which are commonly used in Jahrom region, Iran. The study is descriptive and analytic; making use of Cochran formula, the sample size was estimated as 100 individuals who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sustainable agriculture is pivotal for global farming systems' long-term health and productivity. International case studies, such as those by Constance [53], Abdelrazek and Khafif [54], Ji et al [55], Zarei [56], Charyulu et al [57], and Agbaje et al [46], have thoroughly explored the multifaceted nature of sustainable practices. These investigations emphasize sustainable agriculture's essential role in ensuring agricultural sustainability and addressing pressing environmental issues.…”
Section: Case Studies and Global Examplesmentioning
confidence: 99%
“…Sustainable agriculture is pivotal for global farming systems' long-term health and productivity. International case studies, such as those by Constance [53], Abdelrazek and Khafif [54], Ji et al [55], Zarei [56], Charyulu et al [57], and Agbaje et al [46], have thoroughly explored the multifaceted nature of sustainable practices. These investigations emphasize sustainable agriculture's essential role in ensuring agricultural sustainability and addressing pressing environmental issues.…”
Section: Case Studies and Global Examplesmentioning
confidence: 99%
“…According to 2016 census, the population of the Jahrom county was 228,532, most of them were directly or indirectly associated with agricultural affairs. More than 40% of the farmers are old and have low levels of education (16% of the farmers are illiterate) (Zarei 2017). Jahrom county can be divided into four districts: central, Khafr, Simakan, and Kordian.…”
Section: Study Areamentioning
confidence: 99%
“…Ground water is the main source for irrigation of the agricultural lands. It has been reported that cropping systems in the region are fairly unsustainable (Zarei 2017). Various kinds of dates and citrus plants including orange, tangerine, sour lemon, and sweet lemon, as well as annual crops such as wheat, corn, canola, and many kinds of vegetables and ornamental plants are cultivated in the region.…”
Section: Study Areamentioning
confidence: 99%